Comprehensive Characterization of Viral Diversity of Female Mosquitoes in Madagascar - Amal Bennouna; Michael Luciano Tantely; Vololoniaina Raharinosy; Soa Fy Andriamandimby; Thomas Bigot; Delphine Chrétien; Elise Jacquemet; Stevenn Volant; Sarah Temmam; Philippe Dussart; Vincent Lacoste; Romain Girod; et al. (Viruses, 2023)
The diversity and circulation of arboviruses are not much studied in Madagascar. The fact is that arboviral emergences are rarely detected. The existing surveillance system primarily relies on serological detection and records only a few human infections annually. The city of Mahajanga, however, experienced a confirmed dengue fever epidemic in 2020 and 2021. This study aimed to characterize and analyze the virome of mosquitoes collected in Mahajanga, near patients with dengue-like syndromes to detect known and unknown viruses as well as investigate the factors contributing to the relative low circulation of arboviruses in the area. A total of 4280 mosquitoes representing at least 12 species from the Aedes, Anopheles, and Culex genera were collected during the dry and the rainy seasons from three sites, following an urbanization gradient. The virome analysis of 2192 female mosquitoes identified a diverse range of viral families and genera and revealed different patterns that are signatures of the influence of the mosquito genus or the season of collection on the composition and abundance of the virome. Despite the absence of known human or veterinary arboviruses, the identification and characterization of viral families, genera, and species in the mosquito virome contribute to our understanding of viral ecology and diversity within mosquito populations in Madagascar. This study serves as a foundation for ongoing surveillance efforts and provides a basis for the development of preventive strategies against various mosquito-borne viral diseases, including known arboviruses.